The Primitive, the Aesthetic, and the Savage : An Enlightenment Problematic - Brown, Tony C., 1971- (Book collections on Project MUSE., 2012)
Tony C. Brown examines "the inescapable yet infinitely troubling figure of the not-quite-nothing" in Enlightenment attempts to think about the aesthetic and the savage. The various texts Brown considers-including the writings of Addison, Rousseau, Kant, and Defoe-turn to exotic figures in order to delimit the aesthetic, and to aesthetics in order to comprehend the savage. In his intriguing exploration Brown discovers that the primitive introduces into the aesthetic and the savage an element that proves necessary yet difficult to conceive. At its most profound, Brown explains, thi.